Long-term Outcomes of Treat and Extend Regimen of Anti-vascular Endothelial Growth Factor in Neovascular Age-related Macular Degeneration - Lee, Andy; G Garg, Pooja; T Lyon, Alice; Mirza, Rukhsana; K Gill, Manjot (Journal of Ophthalmic and Vision Research, 2020)
Purpose: This study describes the long-term visual and anatomic outcomes of antivascular endothelial growth factor (VEGF) treatment using a treat and extend dosing regimen. Methods: This cross-sectional cohort study consisted of 224 treatment-naïve eyes with neovascular age-related macular degeneration (NV-AMD) from 202 patients that were treated with anti-VEGF agents bevacizumab, ranibizumab, and aflibercept using a treat and extend (TAE) regimen by four physician investigators in a large urban referral center from 2008 to 2015. Subjects were evaluated for visual acuity, injection frequency, and optical coherence tomography (OCT). Results: Over a seven-year follow-up period (mean 3.4 years), an average 20.2 ± 14.7 injections were administered with 8.4 injections in the first year and 5.5 injections by the seventh year of remaining eyes undergoing treatment. Visual acuity was 0.70 logMAR (20/100 Snellen) at the first visit and 0.67 logMAR (20/93 Snellen) at the final visit, with 74% of eyes maintaining or gaining more than 2 lines of vision. Long-term, 45.1% of eyes achieved 20/50 or better, while 27.1% were 20/200 or worse. Of the treated patients, 61.2% received monotherapy with no difference in visual acuity outcomes or number of injections between the agents used. OCT analysis showed decreased fluid from initial to final follow-up visit: 70.1–15.6% with sub-retinal fluid (SRF) and 47.3–18.8% with intraretinal fluid (IRF) with no difference between the agents were used. Conclusion: This study demonstrates that most patients (74%) improve or maintain visual acuity long-term using a TAE model with a significant portion (45.1%) achieving 20/50 or better visual acuity with sustained treatment.